2014
DOI: 10.1111/1467-8462.12052
|View full text |Cite
|
Sign up to set email alerts
|

Do the Intellectual Property Rights of Importers Matter for Promoting Australian Exports?

Abstract: This article provides the first empirical evidence on the effects of intellectual property rights (IPRs) and threat of imitation on Australia's export flows. Using data from all of Australia's trading partners over the period 1995-2010, an augmented gravity model is estimated in the context of an unbalanced panel. The empirical findings show that level of IPRs of importing countries and threat of imitation posed by the importing countries is both sensitive to Australian bilateral trade flows. These results the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Later research, by Fink and Braga (2005), also suggests a significant and positive impact on bilateral trade flows for the total non-fuel trade aggregate, however IPRs were not found to be significant for high technology trade flows. These and other recent studies (Salim, et al, 2014;Kabir and Salim, 2016) generally resemble those in the literature that have described the links between IPRs protection and bilateral trade. Ivus (2010) analysed trade, pre-and post-TRIPS, and found that the agreement led to an increase in the value of high technology exports from developed countries into developing countries.…”
Section: Introductionsupporting
confidence: 73%
“…Later research, by Fink and Braga (2005), also suggests a significant and positive impact on bilateral trade flows for the total non-fuel trade aggregate, however IPRs were not found to be significant for high technology trade flows. These and other recent studies (Salim, et al, 2014;Kabir and Salim, 2016) generally resemble those in the literature that have described the links between IPRs protection and bilateral trade. Ivus (2010) analysed trade, pre-and post-TRIPS, and found that the agreement led to an increase in the value of high technology exports from developed countries into developing countries.…”
Section: Introductionsupporting
confidence: 73%
“…The primary heads could be done through shirkah/mushārakah (sharing/mutual partnership), qirāḍ/muḍārabah (dormant partnership) and any type of Islamic business transaction. The secondary heads also called redistribution or indirect access to wealth (Salim et al, 2016), involve non-participant beneficiaries in the process of production. The beneficiaries include orphans, widows, children, wayfarer, the poor, the needy etc., all of whom are expected to benefit from the wealth of the wealthy people.…”
Section: Wealth Acquisition In Islam and Position Of Crypto-currencymentioning
confidence: 99%
“…The contribution of this study is two-fold. Firstly, most studies that relate to the issue of trade and IPRs protection covers either accumulated total exports or imports (see Awokuse & Yin 2010;Salim et al 2014) or segregated exports or imports either across sectors or industries (see Maskus & Penubarti 1995;Smith 1999Smith , 2001Smith , 2002, Rafiquzzaman (2002), Awokuse and Yin (2010), Ivus (2010) and Kabir and Salim (2016) and to the best of our knowledge there is limited study using the specific category of capital goods, which embody technology. Therefore, this becomes our first contribution in this study.…”
Section: Introductionmentioning
confidence: 99%